God and reason in the Middle Ages - Grant, Edward, 1926-2020 (Cambridge University Press, 2001)
"The object of this book is twofold: to describe how reason was manifested in the curriculum of medieval universities, especially in the subjects of logic, natural philosophy, and theology; and to explain how the Middle Ages acquired an undeserved reputation as an age of superstition, barbarism, and unreason."--Jacket